Indonesian Penal Policy: Toward Indonesian Criminal Law Reform Based on Pancasila - Najih, Mokhammad (JILS (Journal of Indonesian Legal Studies), 2018)
Criminal law enforcement in Indonesia has always been a very crucial and the sexiest issue. Almost 35 years the idea of criminal law enforcement has been carried out and so far several concepts of the National Criminal Code have been born which continue to experience developmental dynamics that are quite interesting to study. The desire to realize a better criminal law and be able to fulfill the aspirations of the people is the ideal criminal law politics (penal policy). National Criminal Law must have characteristics that are typical of Indonesia, authentic and original, encompassing customary law, systems of values ​​and beliefs, characteristics of modern states and international values. Pancasila as the source of all sources of law, which has not received serious attention needs to be used as a recommendation for the paradigm of penal reform. Pancasila has at least the main principles that must be implemented in all formulations of criminal legislation. These principles are among others, principles based on the source of religious values (Godhead / Divine God), the value of humanity (humanism), the value of unity and peace, the value of democracy and the value of social justice. Therefore, Indonesian criminal law must have values that are based on Pancasila, both in the form of legal norms (addresaat norm), on the types of acts that are regulated (straafbar), in the form of punishment or sanctions (straafmaat), as well as regulatory aspects and implementation of law enforcement law (formal law).